Evaluasi Kemampuan Lahan Rencana Detail Tata Ruang Wilayah Perkotaan Masohi Kabupaten Maluku Tengah - Souhuwat, Jelika Olivia; Siahaya, Willem A.; Osok, Rafael M. (P4W IPB, 2025)
Urban areas are centers of various economic activities as well as public and social services. This causes cities to become dynamic areas with high population density, advanced infrastructure, and rapid changes in land use. However, the development of urban areas does not always have a positive impact and is in harmony with the arrangement of regional spatial use. As a result, the growth of urban areas often does not match land capabilities and is inefficient in terms of space utilization, giving rise to conflicts between sectors. Therefore, the concept of urban area development must be based on the regulation of space use using a sectoral and spatial aspect approach, taking into account functional integration and growth centers. The aim of this study was to assess the land capability of the Masohi’s urban area and to propose management plans to support the implementation of the Detailed Spatial Planning of Masohi, Central Maluku Regency. The method was a survey with the land unit approach. Field observations were carried out in the seven sampled areas representing 125 land units. Land capability analysis was conducted by comparing land characteristics values with the limiting factors according to the criteria for each land capability class. The results showed that the Masohi urban area is located in the III, IV, VI and VII land capability classes, with the limiting factors, the class III are soil depth (k2, k3), and rocks and gravel (b1), the class IV are soil depth (k3), erodibility soil (KE6), and drainage (d3, d4), the class VI erosion rate (e4), and the class VII is erosion (e5). The suitability between land uses in the RDTR and the land capability class are the settlements area is 75.1 ha (70.6%) suitable, and 31.26 ha (29.4%) conditionally suitable, developed areas are 104.2 ha (84.39%) suitable, and 19.27 ha (15.6%) conditionally suitable, opened–space areas are 7.8 ha (87.38 %) suitable, and 1.13 ha (12.6 %), conditionally suitable, while mixed plantations are 266.2 ha (69 %) suitable, and 119.59 ha (31 %) conditionally suitable. Recommendations for managing the Masohi Urban Area’s Detailed Spatial Planning include terracing and improving the city's drainage system.